A Rare but Potentially Fatal Poisoning; Aluminum Phosphide Poisoning - Orkun Tolunay; Tamer Çelik; Gülperi Yücel; Ulaş Özdemir; Anıl Atmış; Asena Sucu; Ümit Çelik (Galenos Yayinevi, 2017)
Phosphide, a very toxic gas, is used in our country as aluminium phosphide tablets impregnated in clay. It is widely used since it has a very high diffusion capacity, whereby it can eradicate all living creatures in any form of their life cycle and does not leave any remnants in agricultural products. Aluminum phosphide poisoning is among intoxications for which there are still no true antidotes. Mortality rate varies between 30% and 100%. This paper presents a case of aluminum phosphide poisoning caused by the uncompleted suicide attempt. A 14-year-old girl, who swallowed aluminum phosphate tablets, was brought to the emergency department with the complaints of nausea and vomiting. The patient was treated with gastric lavage and activated charcoal. Since the patient ingested a lethal amount of aluminum phosphide, she was referred to the pediatric intensive care unit. The patient was discharged in stable condition after supportive care and monitoring. Specific antidotes are life-saving in poisonings. However, this case was presented to show how general treatment principles and quick access to health services affect the result of treatment. Also, we aimed to highlight the uncontrolled selling of aluminum phosphate, which results in high mortality rates in case of poisoning.